Living in the sunlight: micro-environments with higher exposure of sunlight have more abundance and diversity of Hymenoptera in a Brazilian Atlantic Forest fragment - Camila Cristina Ferreira da Costa; Rodrigo Barbosa Gonçalves (Revista Brasileira de Entomologia, 2023)
ABSTRACT Tropical forests are three-dimensional with the presence of numerous micro-environments formed by horizontal and vertical gradients. Such micro-environments can affect the nesting preference of organisms, including the trap-nesting Hymenoptera. Bees and wasps are key elements in ecosystems and are considered as sensitive to environmental changes, and trap-nests sampling methodology is widely used in their ecological and conservation studies. However, many uncertainties remain about nesting site preferences. From this perspective, our aim is to assess the diversity descriptors of trap-nesting Hymenoptera in different micro-environments. The sampling was conducted on three micro-environments (canopy, understory and treefall gaps) replicated on ten permanent plots within a Brazilian Atlantic forest hotspot. In each micro-environment, we installed trap-nest stations made by a set of twenty bamboo artificial nests. We found 762 brood cells from ten wasp and five bee species. The rarefaction curves indicate the lower species richness in understory stations, while treefall gaps and canopy stations were not significantly different. We analyzed abundance, mortality and parasitism rates using generalized linear models, but only abundance varies significantly among micro-environments. Our data indicates that trap-nesting Hymenoptera prefer to nest in micro-environments with higher exposure of sunlight. Canopy and treefall gap assemblages are consistently more abundant and diverse than understory probably due the higher temperature and lower humidity. On the other hand, mortality, parasitism rates, and the species composition were similar among environments. Our hypothesis is that the species composition was not affected as these species have a foraging range that encompasses nearby micro-environments.